The impact of European Monetary Union on the relationship between financial development and growth - Armin, Saeed; Ibrahim, Saifuzzaman; Wan Ngah, Wan Azman Saini (2012)
This study aims to examine the relationship between financial development and economic growth for 15 developed European countries before and after the launch of Euro. The results of the panel data analysis show that financial development is significant in promoting economic growth for both periods. However, the impact of banking sector development on growth is greater in the post-euro period while the impact of stock market development on growth is slightly smaller in that period. The study concludes that the formation of the European Monetary Union (EMU) does not weaken the relationship between financial development and economic growth in the developed European countries.